2022
DOI: 10.1002/slct.202202610
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Third Phase Formation Behaviour of N,N‐Didodecyl‐N’,N’‐Dioctyl Diglycolamide in n‐Dodecane Investigated by Dynamic Light Scattering and FTIR Spectroscopy

Abstract: N,N‐didodecyl‐N’,N’‐dioctyl diglycolamide (D3DODGA) was regarded as a promising ligand for the extraction of trivalent lanthanides and actinides from nuclear waste, owing to the absence of undesirable third phase formation during liquid‐liquid extraction. However, the reason for the absence of third phase formation in D3DODGA as compared to other diglycolamides was not known. To unravel the absence of third phase formation, the extraction behaviour of nitric acid and Nd(III) in 0.2 M D3DODGA in n‐dodecane (n‐D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 36 publications
(124 reference statements)
1
27
0
Order By: Relevance
“…As the Ln-DGA complex C O frequency is red-shifted, this indicates a weaker C O bond associated with the Ln-DGA complex compared to the stronger C O bond in the (DGA)(HNO 3 ) 1-2 adducts. 33 This behavior is not isolated to the systems considered herein, but has been reported with DOHyA, 33 D 3 DODGA, 38 T2EHDGA, 39 TODGA, 33 TODGA (+DHOA), 40 TODGA (+1-octanol), 40 and TODGA (+DOHyA) 33 systems. These studies involved increasing the concentration of Nd at constant extractant and HNO 3 concentrations, where higher Nd concentrations resulted in larger Ds.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…As the Ln-DGA complex C O frequency is red-shifted, this indicates a weaker C O bond associated with the Ln-DGA complex compared to the stronger C O bond in the (DGA)(HNO 3 ) 1-2 adducts. 33 This behavior is not isolated to the systems considered herein, but has been reported with DOHyA, 33 D 3 DODGA, 38 T2EHDGA, 39 TODGA, 33 TODGA (+DHOA), 40 TODGA (+1-octanol), 40 and TODGA (+DOHyA) 33 systems. These studies involved increasing the concentration of Nd at constant extractant and HNO 3 concentrations, where higher Nd concentrations resulted in larger Ds.…”
Section: Resultssupporting
confidence: 51%
“…The systems that experienced a red-shi are consistent with the literature which explains this slight red shi to be the result of hydrogen bond interactions of HNO 3 molecules interacting with polar carbonyl group of TODGA, forming (DGA)(HNO 3 ) 1-2 adducts. 30,37,38 Across the varying alkyl chain lengths of 1-alcohol, the trend in this red-shied C]O frequency for 5 vol% is 1-hexanol < 1-octanol < 1-decanol. Increasing the 1-alcohol concentration to 30 vol% results in the reverse trend, 1-decanol < 1-octanol < 1-hexanol.…”
Section: Ft-ir Analysismentioning
confidence: 98%
“…33,35 According to literature, DGAs can form inverse micelles with polar molecules (e.g., HNO 3 ) in long-chain alkane diluents (e.g., n-dodecane or n-octane). 33,36,37 Massey et al found that the addition of n-octanol reduced the degree of aggregation and hence reduced the degree of 3 rd phase formation. 34 In our experiments, even at 10 mol L À1 HNO 3 , no 3 rd phase formation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The steric hindrance from the substitution in the backbone seems to reduce the probability of increasing aggregate and cluster formation in solution, hence reducing the possibility of third-phase formation at high nitric acid concentrations. 33,34,37 Low distribution ratios are not necessarily a disadvantage, as for a process application it must also be possible to back-extract the desired metal ions from the loaded organic phase. Nevertheless, the distribution ratios of the ligands considered here are quite low at a ligand concentration of 0.1 mol L À1 for the trivalent metal ions and associated with high uncertainties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation